EASYWAVE UNTUK PERAMALAN DATA GELOMBANG LAUT BERBASIS PEMOGRAMAN PYTHON DENGAN METODE SVERRUP, MUNK AND BRETSCHNEIDER (SMB) (Studi Kasus : Perairan Sungairaden, Kalimantan Timur) - Ghifari Raihan Silam; Sekar Adiningsih; Yoas Heryanto (Jurnal Meteorologi Klimatologi dan Geofisika, 2020)
Manual ocean wave data forecasting takes a long time so automation is needed to increase time efficiency. Easywave is an algorithm written in Python programming language and can be used to analyse data including ocean wave forecasting using SMB method. The data that used is the wind speed component for 4 seasons from January 2008 until December 2018 which downloaded through the forecast data provider site from European Centre for Medium-Range Weather Forecasts (ECMWF). The research location is adjusted with the location of the comparative data to perceive the accuracy of the constructed algorithm through comparison result with field observation data, which located in Sungairaden, Sub-District of Samboja, District of Kutai Kartanegara, East Kalimantan Province . The forecasting result shows the significant wave height (Hs) and the significant wave period (Ts) for West season, Fisrt Transition season, East season and Second Transition season are 0,55 m; 0,54 m; 0,79 m; 0,76 m and 3,85 s; 3,81 s; 4,61 s; 4,51 s. The wave height that will be formed when the wave moves towards shallow water is obtained a value of 0,576; 0,564; 0,887; and 0,846 meter. The wave energy flux that occurs in each season is 0,74; 0,70; 2,11; 1,92 kW/m